2018
DOI: 10.1534/genetics.118.301592
|View full text |Cite
|
Sign up to set email alerts
|

Performing Parentage Analysis in the Presence of Inbreeding and Null Alleles

Abstract: Parentage analysis is an important method that is used widely in zoological and ecological studies. Current mathematical models of parentage analyses usually assume that a population has a uniform genetic structure and that mating is panmictic. In a natural population, the geographic or social structure of a population, and/or nonrandom mating, usually leads to a genetic structure and results in genotypic frequencies deviating from those expected under the Hardy-Weinberg equilibrium (HWE). In addition, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The assumptions of Mendelian inheritance and Hardy-Weinberg equilibrium of parental genotypes [18] are also limitations of parentage analysis techniques (but see [3436]) for methods that relax the assumption of Hardy-Weinberg equilibrium). These assumptions may be violated by many factors, particularly during MDA programmes [7072].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumptions of Mendelian inheritance and Hardy-Weinberg equilibrium of parental genotypes [18] are also limitations of parentage analysis techniques (but see [3436]) for methods that relax the assumption of Hardy-Weinberg equilibrium). These assumptions may be violated by many factors, particularly during MDA programmes [7072].…”
Section: Discussionmentioning
confidence: 99%
“…Sibship reconstruction techniques depend fundamentally on the rules of Mendelian inheritance and frequently on the assumption that parental genotypes comprising a host’s worm burden exist at Hardy-Weinberg equilibrium [18]. Inbreeding, population bottlenecks and linkage disequilibrium of neutral markers proximate to genes under natural selection often violate these assumptions and are well discussed in the literature [33, 34], including parentage methods that relax the assumption of Hardy-Weinberg equilibrium and account for inbreeding [3436]. But statistical questions that arise when using sibship reconstruction to infer the number of fecund adults have received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Weighted genotype‐based methods are based on the weighting of extracted genotypes according to their posterior probabilities. These methods are allele frequency estimation based on an EM algorithm (De Silva, Hall, Rikkerink, McNeilage, & Fraser, ; Kalinowski & Taper, ), genetic diversity analysis, parentage analysis (Huang, Mi, Dunn, Wang, & Li, ; Kalinowski, Taper, & Marshall, ), kinship coefficient estimation (Loiselle, Sork, Nason, & Graham, ; Ritland, ; Weir, ), and pairwise relatedness coefficient estimation (Huang, Guo, et al, ; Huang, Ritland, et al, ; Huang et al, ). The effects of null alleles, negative amplification and self‐fertilization can be freely taken into account in most methods, which use the genotypic and phenotypic frequencies.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we estimated pairwise relatedness using a population genetic method, in which identical-by-descent (IBD) statistics between dyads are determined based on the estimation of allele frequencies at each SNP under Hardy-Weinberg Equilibrium (HWE) assumptions. Because population substructures and high levels of inbreeding deviate from the HWE and thus affect parental analysis ( Huang et al, 2018 ), we ascertained several population genetic estimates, such as observed and expected heterozygosity of genotypes, inbreeding coefficients (F IS ), and population substructures for the study population using POLYRELATEDNESS v1.4 ( Huang et al, 2016 ). We estimated the relatedness of all samples in all nests using KING v2.1.3 ( Manichaikul et al, 2010 ).…”
mentioning
confidence: 99%
“…The observed and expected heterozygosities of genotypes were 0.1012 and 0.1277, respectively. The estimated inbreeding coefficient (F IS ) was 0.166, suggesting a low level of inbreeding, which may have a neglected effect on parental analysis ( Huang et al, 2018 ). In addition, we did not detect any population substructure signatures (global F st =0), meaning that the overall samples could be treated as a single population.…”
mentioning
confidence: 99%